Developing Interest in Studying in Low Performing College Students: Analysis of Modern Teaching Practice - I U Gajibalayeva (Peoples' Friendship University of Russia (RUDN University), 2011)
The results of the survey conducted among the teachers of colleges are analyzed and the interpretation of the statistical data on the problem of developing the interest in studying in low performing students of college is submitted in the article.